2008
DOI: 10.1200/jco.2007.14.2851
|View full text |Cite
|
Sign up to set email alerts
|

Implementing a Survivorship Care Plan for Patients With Breast Cancer

Abstract: Breast cancer survivors account for 23% of the more than 10 million cancer survivors in the United States today. The treatments for breast cancer are complex and extend over a long period of time. The post-treatment period is characterized by gradual recovery from many adverse effects from treatment; however, many symptoms and problems persist as late effects (eg, infertility, menopausal symptoms, fatigue), and there may be less frequent long-term effects (eg, second cancers, lymphedema, osteoporosis). There i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
180
0
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 240 publications
(187 citation statements)
references
References 39 publications
(16 reference statements)
2
180
0
3
Order By: Relevance
“…Similarly, emerging research suggests that an SCP should include (1) a treatment summary describing the cancer diagnosis, histology, stage, and primary treatments given [12,13] and (2) a follow-up care plan, which includes information on recovery from treatment and the need for ongoing health maintenance or other recommended therapies to optimize continuity and coordination of care [14]. Finally, the literature also suggests that an optimal SCP should be personalized and patient-centered [10][11][12][13]. In summary, SCPs can serve to facilitate the transfer of knowledge between health care providers and patients, potentially increasing patients' knowledge of and adherence to posttreatment surveillance and follow-up care recommendations [8,15].…”
mentioning
confidence: 99%
“…Similarly, emerging research suggests that an SCP should include (1) a treatment summary describing the cancer diagnosis, histology, stage, and primary treatments given [12,13] and (2) a follow-up care plan, which includes information on recovery from treatment and the need for ongoing health maintenance or other recommended therapies to optimize continuity and coordination of care [14]. Finally, the literature also suggests that an optimal SCP should be personalized and patient-centered [10][11][12][13]. In summary, SCPs can serve to facilitate the transfer of knowledge between health care providers and patients, potentially increasing patients' knowledge of and adherence to posttreatment surveillance and follow-up care recommendations [8,15].…”
mentioning
confidence: 99%
“…1,2 In response, various supportive psychosocial intervention strategies have been designed, tailored to the problems that cancer patients face during the course of their disease. [3][4][5][6] The extent to which cancer affects not only patients but also their closest relatives was first addressed in a seminal article published more than 20 years ago, in which House et al illustrated how several diseases can influence people close to the patient. 7 The mechanism of this effect may involve several interacting pathways: the event may cause stress in the partner; it might deprive the partner of emotional, social, and economic support; and it can influence the daily life and behavior of the partner.…”
mentioning
confidence: 99%
“…cancer.gov) and recent data have shown that the incidence of breast cancer diagnosed in young women is increasing (Merlo et al 2012). The increasing number of earlier diagnosis and adjuvant therapy are expected to increase the number of breast cancer survivors (Jemal et al 2003, Ganz & Hahn 2008. In young women, chemotherapy may induce amenorrhea and it is still uncertain how to assess menopausal status in these patients despite the fact that the definition of the menopausal status is relevant for choosing appropriate antihormonal treatment (Amir et al 2009(Amir et al , 2010.…”
Section: Introductionmentioning
confidence: 99%